The Concept of Apartheid: Its Dimensions and Dangers - أبو قصة, محمد (Dirasat in Economics and Business, 1981)
The paper will give a glance to the development of the concept of Apartheid and its roots in this African territory called South Africa. This contagious and dangerous issue seems to represent a serious challenge not only to Africa but to the world at large as well. This apartheid which is considered an ideology and national policy of the white racist regime of Pretoria in South Africa has its own dimensions. Therefore, the aim of this paper is to examine and analyse the behaviour of the South African regime in dealing with this issue vis-a-vis its planned policy of white supremacy and black African inferiority, humiliation and violation of human rights and inhuman acts that are committed against the black African majority. The paper will also show the degree of connivance of the western regimes and their allies and the "M.N.C." with the Pretoria regime and their involvement and active role in maintaining the status quo. The paper will also explain the role of the reaction of the African countries who achieved their independence within the last two consecutive decades and their attitude towards this type of concern which is threatening their existence and survival as entities. The paper will also show how the African leaders seem to cope with such a problem and their connection with South African and other western capitals and to show how the black Africans which constitute the majority are suffering from exploitation and unjust conditions and how they became disadvantaged, under-priveleged, culturally deprived and completely de- pressed groups of people who are the original inhabitants of the area.